Fontes e doses de fósforo na formação de mudas de mamoeiro (Carica Papaya l.) em solos de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The Amazon also expresses deficiency related to meet the nutritional requirements of papaya in its various production stages, where the quality of seedlings is a major hurdle in the production chain of papaya studies. This study investigated the effect of two phosphate sources with increasing doses of fertilizers in the formation of papaya seedlings. The experimental design was completely randomized with three replications, with analysis in 2x2x5 factorial arrangement. The factors were two levels in soils (Red Yellow Ultisoil dystrophic medium texture and Yellow Oxisoil dystrophic clayey texture), source at two levels (TFY - magnesium thermophosphate Yoorin, 18,1% P2O5 and FNRA - Arad phosphate reactive, 33,1 % P2O5) and doses at five levels (50, 75, 150, 300, 600 mg P dm-3). Each experimental plot consisted of a plant. The initial growth of papaya is affected by different phosphorus sources. In the production of seedlings for each dm3 substrate the recommendation is 331,90 mg P using thermophosphate yoorin is 451,64 mg of P using the reactive phosphate Arad in Ultisoil. In Oxisoil the recommendation is 374,75 mg of P using thermophosphate Yoorin is 205,41 mg of P using the reactive phosphate Arad. The species showed potential responsive to phosphorus fertilization.
Keywords: Mamão; Fruticultura; Adubação fosfatada; Papaya; Fruticulture; Phosphorus fertilization; Carica Papaya l. (Mamoeiro); CIÊNCIAS AGRÁRIAS: AGRONOMIA